Biomechanical analysis of parachute speed-resisted training on sprint performance: A single subject study - Seckold, T. (Journal of Australian Strength and Conditioning, 2012)
Parachutes are a widely used form of speed resisted sprint training, with the aim of developing acceleration. Acceleration is of particular importance to field sport athletes, thus explaining its popularity as a training modality. Regardless of its popularity, little is known of the biomechanical impacts of parachute sprint resisted training. The purpose of this study was to identify the acute biomechanical impacts of parachute sprint resisted training, in comparison with normal sprint running. A single male subject was required to perform a number of parachute resisted and un-resisted sprint efforts over a distance of 26m. A high-speed video camera was located at the 17m mark for later analysis. Joint angles of the hip, knee and ankle were assessed during the various phases of the sprint cycle. Results from this study indicate that there are little biomechanical differences between parachute resisted and un-resisted methods, however parachute methods appear to result in greater hip flexion and braking forces as a result of overstriding. Conclusions from this study indicate that parachute training is an effective form of movement specific resistance training. Although effective, sled training is recommended as the preferable form of sprint resisted training.